Anti-shrinkage micro-crack self-healing geopolymer composite material and preparation method thereof
Patent Information
- Application Number
- CN202611087043.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的目的在于克服现有技术不足,提供一种抗干缩微裂纹自愈合地质聚合物复合材料及其制备方法,解决现有地质聚合物干燥收缩大、易开裂、自修复体系耐碱性差、单一技术无法实现全周期抗裂修复等问题
本发明自修复微胶囊采用多孔无机微载体负载硅酸钠修复剂,外层包覆脲醛树脂、三聚氰胺甲醛树脂等耐碱性高分子壁材,双层结构可有效隔绝地质聚合物强碱环境,避免壁材被侵蚀、修复剂提前泄漏;硅酸钠修复剂与地质聚合物基体化学相容性高,开裂后快速反应生成胶凝产物封堵微裂纹。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a self-healing geopolymer composite material resistant to shrinkage microcracks and its preparation method. Background Technology
[0002] Geopolymers are a new type of inorganic cementitious material formed by alkali activation using industrial solid wastes such as fly ash, slag, and silica fume as the main raw materials. They have advantages such as high early strength, good durability, and green and low carbon emissions. However, two inherent defects limit their engineering applications: first, they are brittle and prone to microcracks under load; second, the drying shrinkage during the hardening process is significant, and the shrinkage stress directly induces microcracks and exacerbates the propagation of load-bearing cracks.
[0003] Existing technologies mostly focus on single problems: adding fibers to toughen and prevent cracking; incorporating expanding agents to compensate for drying shrinkage; introducing microcapsules to achieve self-repair of cracks. However, these methods are mostly single-effect and do not form a synergistic effect. Single expanding agents are prone to improper expansion timing and excessive expansion force, which can damage the matrix. Simple self-repair can only passively repair existing cracks and cannot inhibit the continuous generation of new cracks due to shrinkage stress.
[0004] In addition, conventional self-healing microcapsule wall materials have poor alkali resistance and are easily corroded and prematurely ruptured in the strong alkaline environment of geopolymers, causing the repair agent to leak prematurely and fail to function properly when cracks occur.
[0005] Therefore, developing a geopolymer composite material that can suppress shrinkage cracks at the source, autonomously repair microcracks during service life, and exhibit excellent alkali resistance and significant synergistic effects is of great significance for improving the volume stability and long-term durability of materials. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a self-healing geopolymer composite material with anti-drying shrinkage microcracks and its preparation method, thereby solving the problems of large drying shrinkage, easy cracking, poor alkali resistance of the self-healing system, and inability of a single technology to achieve full-cycle crack resistance and repair in existing geopolymers.
[0007] The present invention adopts the following technical solution: A self-healing geopolymer composite material resistant to shrinkage microcracks, comprising, by weight parts: 90-100 parts of active silica-alumina raw material; 35-55 parts of alkaline activator; 4-8 parts of expanding agent; 3-5 portions of self-repairing microcapsules; 1 to 1.5 parts of reinforcing fiber; The alkali activator is a compound solution of sodium silicate and sodium hydroxide, the modulus of the alkali activator is 1.2-1.8, and the alkali activator accounts for 6%-10% of the total solid mass of the self-healing geopolymer composite material for resisting shrinkage microcracks, based on sodium oxide. The expanding agent is a coated and modified active magnesium oxide, and the expanding agent is active magnesium oxide with a passivation layer of magnesium carbonate, basic magnesium carbonate or magnesium hydroxide on its surface. The self-healing microcapsule comprises a porous inorganic microcarrier, a sodium silicate repair agent loaded in the pores of the porous inorganic microcarrier, and an alkali-resistant material coating the outer surface of the porous inorganic microcarrier.
[0008] Further, by mass parts, the active silica-alumina raw material includes: 60-70 parts fly ash, 20-30 parts slag, and 5-15 parts silica fume.
[0009] Furthermore, the sodium silicate has a modulus of 3.0-3.5; and the sodium hydroxide has a purity of not less than 99%.
[0010] Furthermore, the alkali-resistant material is urea-formaldehyde resin or melamine-formaldehyde resin.
[0011] Furthermore, the thickness of the alkali-resistant polymer wall material is 2μm to 10μm, and the particle size of the self-healing microcapsules is 50μm to 200μm.
[0012] Furthermore, the sodium silicate repair agent is a sodium silicate solution with a modulus of 2.5-3 and a solid content of 40%.
[0013] Furthermore, the reinforcing fiber is one or more of basalt fiber, polyvinyl alcohol fiber, or polypropylene fiber, and the length of the reinforcing fiber is 6mm to 9mm.
[0014] The present invention also provides a method for preparing the above-mentioned composite material, comprising the following steps: Step 0: Mix fly ash, slag, and silica fume evenly to obtain the active aluminosilicate raw material; The sodium silicate and sodium hydroxide are compounded to form an alkaline activator with a modulus of 1.2-1.8; The active magnesium oxide is surface passivated in an atmosphere containing carbon dioxide and water vapor to form a passivation layer of magnesium carbonate, basic magnesium carbonate, or magnesium hydroxide on its surface. After drying, grinding, and sieving, the expanding agent is obtained. The dried porous inorganic microcarrier is immersed in sodium silicate repair agent. The sodium silicate repair agent is loaded into its pores by impregnation under normal pressure or vacuum. After removing the free liquid on the surface, the outer surface of the porous inorganic microcarrier is coated with the alkali-resistant material. After curing, drying and sieving, the self-healing microcapsules are obtained. Step 1: Add the expanding agent and the reinforcing fiber to the active aluminosilicate raw material, stir, and obtain a solid mixture; Step 2: Add the self-healing microcapsules to the solid mixture and continue stirring to obtain a dry mixture; Step 3: Slowly add the alkali activator to the dry mixture. The alkali activator accounts for 6%-10% of the mass of the dry mixture, based on sodium oxide. Stir to obtain the self-healing geopolymer composite material with anti-drying microcracks.
[0015] Compared with the prior art, the present invention has the following advantages: The self-healing microcapsules of this invention use porous inorganic microcarriers to load sodium silicate repair agent, and are coated with alkali-resistant polymer wall materials such as urea-formaldehyde resin and melamine-formaldehyde resin. The double-layer structure can effectively isolate the strong alkaline environment of the geopolymer, avoiding the wall material from being eroded and the repair agent from premature leakage. The sodium silicate repair agent has high chemical compatibility with the geopolymer matrix, and reacts quickly after cracking to generate gel products to seal microcracks.
[0016] Active magnesium oxide is passivated in a CO2 and water vapor atmosphere, forming a passivation layer of magnesium carbonate, basic magnesium carbonate, or magnesium hydroxide on its surface. This allows for controlled expansion, with early and moderate expansion compensating for the hardening and drying shrinkage of the geopolymer. This reduces shrinkage cracks from the source and prevents unmodified magnesium oxide from expanding too quickly and causing excessive expansion force that could damage the matrix structure.
[0017] The expansion agent inhibits cracking and the microcapsule self-repair forms a full-cycle synergistic crack resistance system: the expansion agent significantly reduces the number and width of the matrix's original shrinkage microcracks, reducing the repair load of the microcapsule; the microcapsule repair product densifies the matrix pores, inhibiting the generation of new cracks in the later stage; the synergy of the two makes the strength recovery rate and impermeability recovery rate much higher than the simple superposition of single components.
[0018] The 28-day drying shrinkage rate of the composite material is significantly reduced, the initiation and propagation of microcracks are effectively controlled, and the material's impermeability, freeze-thaw resistance, and long-term mechanical stability are significantly improved, which can significantly extend the service life of engineering structures. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.
[0021] The following specific embodiments further illustrate the present invention, but are not intended to limit the invention.
[0022] The specifications and sources of the raw materials used in the embodiments of this invention are as follows: Fly ash: Grade I fly ash, Henan Borun Foundry Materials Co., Ltd.; Slag: S95 grade granulated blast furnace slag powder, Tangshan Caofeidian Dunshi New Building Materials Co., Ltd.; Silica fume: SF-92, Xining Chengzeyuan Environmental Protection Technology Co., Ltd.; Activated magnesium oxide: MgO-150, active content 92%, Xingtai Magnesium Source Chemical Co., Ltd. Alkali activator: Sodium silicate solution (modulus 3.3, solid content 34%), flake sodium hydroxide (purity 99%), Jinan Xinpengyuan Chemical Co., Ltd.; Porous inorganic microcarriers: porous diatomaceous earth microspheres; Self-healing microcapsules: using porous diatomaceous earth microspheres as carriers, internally loaded with sodium silicate repair agent with a modulus of 2.8 and a solid content of 40%, and coated with urea-formaldehyde resin / melamine-formaldehyde resin on the outside, with a particle size of 50~200μm and a wall thickness of 2~10μm; Basalt fiber: 6mm in length, Shanghai Armor New Material Technology Co., Ltd. Polyvinyl alcohol fiber (PVA): 6mm in length, K-II type, Kuraray Corporation, Japan; Polypropylene fiber (PP): 9mm in length, Shenzhen Huayu New Materials Co., Ltd.
[0023] Example 1 This embodiment 1 provides a self-healing geopolymer composite material resistant to shrinkage microcracks, which, by mass parts: Activated silica-alumina raw materials: 70 parts fly ash, 20 parts slag, and 10 parts silica fume; Alkali activator: a compound of sodium silicate and sodium hydroxide, modulus 1.5, alkali equivalent of 8% based on sodium oxide; Expanding agent: 4 parts of active magnesium oxide passivated and modified by CO2 and water vapor atmosphere; Self-healing microcapsules: Three portions of porous inorganic microcarrier sodium silicate microcapsules coated with urea-formaldehyde resin; Reinforcing fiber: 1 part basalt fiber.
[0024] The following is a method for preparing a self-healing geopolymer composite material resistant to shrinkage microcracks in Example 1: Step 0: Mix fly ash, slag, and silica fume evenly according to the specified ratio to obtain active silica-alumina raw material; combine sodium silicate solution with 3.3 modulus and 99% pure flake sodium hydroxide, adjust to modulus 1.5, stir until sodium hydroxide is completely dissolved, and let stand and cool to room temperature for later use. Active magnesium oxide (MgO-150, active content 92%) was passivated in a closed atmosphere containing carbon dioxide and water vapor to form a magnesium carbonate passivation layer on the surface. After drying, grinding and sieving, a passivated modified active magnesium oxide expander was obtained. Dry porous diatomaceous earth microcarriers were immersed in a sodium silicate solution with a modulus of 2.8 and a solid content of 40%, and then vacuum impregnated with a repair agent. The free sodium silicate liquid on the surface was wiped off. The outer surface of the microcarriers was coated with urea-formaldehyde resin, cured, dried, and sieved to obtain self-healing microcapsules with a particle size of 50~200μm and a wall thickness of 2~10μm.
[0025] In this invention, the modulus is the sodium silicate modulus n = SiO2 / Na2O (molar ratio), and the specific definition and test method are as follows (GB / T4209-2022).
[0026] Step 1: Add passivated modified active magnesium oxide expansion agent and basalt fiber with a length of 6mm to the active silicon-aluminum raw material, put it into a mixer and stir for 3 minutes to obtain a solid mixture.
[0027] Step 2: Add urea-formaldehyde resin to the solid mixture to coat porous inorganic microcarrier self-healing microcapsules, and continue stirring for 2 minutes to ensure uniform dispersion of the microcapsules, thus obtaining a dry mixture.
[0028] Step 3: Add the alkali activator cooled to room temperature to the dry mix, control the alkali equivalent (based on sodium oxide) to be 8% of the total solid mass, and continue stirring for 4 minutes to obtain a self-healing geopolymer composite material resistant to shrinkage microcracks.
[0029] Step 4: Pour the self-healing geopolymer composite material with anti-drying shrinkage microcracks into a 40mm×40mm×160mm triple mold, place it on a vibration table and vibrate for 60s to fully remove air bubbles inside the slurry; smooth the upper surface of the mold with a scraper, cover it with plastic wrap to seal and prevent moisture loss; after curing at room temperature for 24 hours, carefully demold it; transfer the demolded specimen to a standard curing room and cure it at a temperature of 20±2℃ and a relative humidity of ≥95% until the specified age.
[0030] The drying shrinkage, mechanical properties, self-healing properties, and freeze-thaw resistance of the composite material obtained in this embodiment were tested according to national and industry standard methods. The test results are shown in Table 1 below: Table 1 Performance Indicators of Composite Material in Example 1
[0031] It should be noted that the self-healing efficiency test method is as follows: the specimens cured to 28 days are preloaded using the three-point bending method to induce an initial microcrack with a width of 0.2 mm; the pre-cracked specimens are then placed in a standard curing environment with a temperature of 20±2℃ and a relative humidity of ≥95% for another 28 days to allow them to complete self-healing. The initial flexural strength of the specimen before cracking and the flexural strength after repair were measured separately, and the strength recovery rate was calculated according to the following formula: Strength recovery rate (%) = (flexural strength after repair ÷ initial flexural strength before cracking) × 100%.
[0032] Example 2 This embodiment 2 provides a self-healing geopolymer composite material resistant to shrinkage microcracks, which, by mass parts: Activated silica-alumina raw materials: 65 parts fly ash, 25 parts slag, and 10 parts silica fume; Alkali activator: a compound of sodium silicate and sodium hydroxide, modulus 1.5, alkali equivalent of 8% based on sodium oxide; Expanding agent: 6 parts of active magnesium oxide passivated and modified by CO2 + water vapor atmosphere; Self-healing microcapsules: Four portions of porous inorganic microcarrier sodium silicate microcapsules coated with urea-formaldehyde resin; Reinforcing fiber: 1 part basalt fiber.
[0033] The following is a method for preparing a self-healing geopolymer composite material resistant to shrinkage microcracks in Example 2: Step 0: Mix fly ash, slag, and silica fume evenly according to the specified ratio to obtain active silica-alumina raw material; combine sodium silicate solution with 3.3 modulus and 99% pure flake sodium hydroxide, adjust to modulus 1.5, stir until sodium hydroxide is completely dissolved, and let stand and cool to room temperature for later use. Active magnesium oxide is passivated in an atmosphere containing carbon dioxide and water vapor to form a basic magnesium carbonate passivation layer on the surface. After drying, grinding and sieving, an expansion agent is obtained. Self-healing microcapsules with particle sizes of 50-200 μm and wall thicknesses of 2-10 μm were prepared using porous diatomaceous earth microspheres as carriers, sodium silicate solution with a modulus of 2.8 and a solid content of 40% as a repair agent, and urea-formaldehyde resin as the outer wall material.
[0034] Step 1: Add passivated modified active magnesium oxide expansion agent and basalt fiber with a length of 6mm to the active silicon-aluminum raw material, put it into a mixer and stir for 3 minutes to obtain a solid mixture.
[0035] Step 2: Add urea-formaldehyde resin to the solid mixture to coat porous inorganic microcarrier self-healing microcapsules, and continue stirring for 2 minutes to ensure uniform dispersion of the microcapsules, thus obtaining a dry mixture.
[0036] Step 3: Add the alkali activator cooled to room temperature to the dry mix, control the alkali equivalent (based on sodium oxide) to be 8% of the total solid mass, and continue stirring for 4 minutes to obtain a self-healing geopolymer composite material resistant to shrinkage microcracks.
[0037] Step 4: Pour the self-healing geopolymer composite material with anti-drying shrinkage microcracks into a 40mm×40mm×160mm triple mold, place it on a vibration table and vibrate for 60s to fully remove air bubbles inside the slurry; smooth the upper surface of the mold with a scraper, cover it with plastic wrap to seal and prevent moisture loss; after curing at room temperature for 24 hours, carefully demold it; transfer the demolded specimen to a standard curing room and cure it at a temperature of 20±2℃ and a relative humidity of ≥95% until the specified age.
[0038] The composite material obtained in this example was subjected to comprehensive performance tests using the same test standards and methods as in Example 1. The test results are shown in Table 2 below: Table 2 Performance indicators of composite materials in Example 2
[0039] Example 3 This embodiment 3 provides a self-healing geopolymer composite material resistant to shrinkage microcracks, which, by mass parts: Activated silica-alumina raw materials: 60 parts fly ash, 30 parts slag, and 10 parts silica fume; Alkali activator: a compound of sodium silicate and sodium hydroxide, modulus 1.5, alkali equivalent of 8% based on sodium oxide; Expanding agent: 8 parts of active magnesium oxide passivated and modified by CO2 and water vapor atmosphere; Self-healing microcapsules: Five portions of porous inorganic microcarrier sodium silicate microcapsules coated with melamine-formaldehyde resin; Reinforcing fiber: 1.5 parts polyvinyl alcohol fiber.
[0040] The following is a method for preparing a self-healing geopolymer composite material resistant to shrinkage microcracks in Example 3 of this paper: Step 0: Mix fly ash, slag, and silica fume evenly according to the specified ratio to obtain active silica-alumina raw material; combine sodium silicate solution with 3.3 modulus and 99% pure flake sodium hydroxide, adjust to modulus 1.5, stir until sodium hydroxide is completely dissolved, and let stand and cool to room temperature for later use. Active magnesium oxide is passivated in a carbon dioxide + water vapor atmosphere to form a magnesium hydroxide passivation layer on the surface. After drying, grinding and sieving, an expansion agent is obtained. Self-healing microcapsules with particle size of 50-200 μm and wall thickness of 2-10 μm were prepared using porous diatomaceous earth microspheres as carriers, sodium silicate solution with modulus of 2.8 and solid content of 40% as repair agent, and melamine-formaldehyde resin as outer wall material.
[0041] Step 1: Add passivated modified active magnesium oxide expansion agent and 6mm long polyvinyl alcohol fiber to the active silicon aluminum raw material, put it into a mixer and stir for 3 minutes to obtain a solid mixture.
[0042] Step 2: Add melamine-formaldehyde resin-coated porous inorganic microcarrier self-healing microcapsules to the solid mixture, and continue stirring for 2 minutes to ensure uniform dispersion of the microcapsules, thus obtaining a dry mixture.
[0043] Step 3: Add the alkali activator cooled to room temperature to the dry mix, control the alkali equivalent (based on sodium oxide) to be 8% of the total solid mass, and continue stirring for 4 minutes to obtain a self-healing geopolymer composite material resistant to shrinkage microcracks.
[0044] Step 4: Immediately pour the slurry into a 40mm×40mm×160mm triple mold, place it on a vibrating table and vibrate for 60 seconds to fully remove air bubbles from the slurry; smooth the upper surface of the mold with a scraper, cover it with plastic wrap to seal and prevent moisture loss; after curing at room temperature for 24 hours, carefully demold the specimen; transfer the demolded specimen to a standard curing room and cure it at a temperature of 20±2℃ and a relative humidity of ≥95% until the specified age.
[0045] Following the same test conditions and standards as in Example 1, the composite material obtained in this example was tested for drying shrinkage, mechanical properties, self-healing properties, and durability. The test results are shown in Table 3 below. Table 3 Performance indicators of composite materials in Example 3
[0046] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that no coated modified active magnesium oxide expanding agent was added.
[0047] The specifications and sources of the raw materials are the same as in Example 2.
[0048] The preparation method is the same as in Example 2, except that no active magnesium oxide expanding agent is added in step one, and the remaining steps and parameters are completely consistent.
[0049] The material obtained in this comparative example was subjected to performance tests using the same test methods and evaluation criteria as in Example 2. The test results are shown in Table 4 below: Table 4 Performance indicators of the composite material in Comparative Example 1
[0050] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that no self-healing microcapsules were added.
[0051] The specifications and sources of the raw materials are the same as in Example 2.
[0052] The preparation method is the same as in Example 2, except that self-healing microcapsules are not added in step two, and the remaining steps and parameters are completely consistent.
[0053] Using the same test conditions and standards as in Example 2, various performance tests were conducted on the comparative example material. The test results are shown in Table 5 below: Table 5 Performance indicators of the composite materials in Comparative Example 2
[0054] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that no expanding agent or self-healing microcapsules were added.
[0055] The specifications and sources of the raw materials are the same as in Example 2.
[0056] The preparation method is the same as in Example 2, except that no expanding agent is added in step one and no microcapsules are added in step two, and the remaining steps and parameters are completely consistent.
[0057] Using Example 2 as a control, the same test method was used to test the performance of the blank sample of this comparative example. The test results are shown in Table 6 below: Table 6 Performance indicators of the composite materials in Comparative Example 3
[0058] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that the microcapsule wall material is gelatin (not alkali resistant).
[0059] The specifications and sources of the raw materials are the same as in Example 2.
[0060] The preparation method is the same as in Example 2, except that the urea-formaldehyde resin wall material is replaced with gelatin, and the remaining steps and parameters are completely consistent.
[0061] Using the same test standards as in Example 2, the effect of the wall material's alkali resistance on the material properties was investigated. The test results are shown in Table 7 below: Table 7 Performance indicators of the composite materials in Comparative Example 4
[0062] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that the expanding agent is unpassivated modified active magnesium oxide (without magnesium carbonate, basic magnesium carbonate, or magnesium hydroxide passivation layer).
[0063] The specifications and sources of the raw materials are the same as in Example 2.
[0064] The preparation method is the same as in Example 2, except that unpassivated native active magnesium oxide is added in step one, and the remaining steps and parameters are completely consistent.
[0065] The effect of the expansion agent passivation treatment on the material properties was investigated using the same test method as in Example 2. The test results are shown in Table 8 below: Table 8 Performance indicators of the composite materials in Comparative Example 5
[0066] In summary, to verify the synergistic effect of the expansion component and the self-healing component, Comparative Example 3 was used as the reference sample, and the drying shrinkage reduction value and self-healing strength recovery rate of each group of materials were compared and analyzed. The results are shown in Table 9 below.
[0067] Table 9 Comparative Analysis of Synergistic Effects
[0068] It should be noted that: shrinkage reduction value = 28-day shrinkage rate of Comparative Example 3 - 28-day shrinkage rate of each group; As shown in Table 9 above, in terms of drying shrinkage compensation, the shrinkage reduction value of Comparative Example 1 (with only the addition of self-healing microcapsules) was only 17 × 10⁻⁶. -6 The shrinkage reduction value of Comparative Example 2 (with only the addition of expanding agent) was 320 × 10⁻⁶. -6 The simple sum of the contraction reduction values of the two is 337 × 10⁻⁶. -6 Example 2 (with simultaneous addition of a swelling agent and self-healing microcapsules) showed an actual shrinkage reduction of 333 × 10⁻⁶. -6 The value is close to the sum of the above simple values, indicating that the swelling agent and the self-healing microcapsules mainly exhibit a superimposed effect in terms of drying shrinkage compensation performance.
[0069] Regarding self-healing efficiency, the strength recovery rate of Comparative Example 1 was 68%, and the strength recovery rate of Comparative Example 2 was 11%, with a simple sum of the two strength recovery rates of 79%; while the actual strength recovery rate of Example 2 reached 86%, which was significantly higher than the simple sum of the two.
[0070] The above results fully demonstrate that the swelling agent and the self-healing microcapsules have a significant synergistic enhancement effect on self-healing performance.
[0071] Its mechanism of action is as follows: the expansion component plays a volume compensation role in the early stage of material hardening, reducing the number and width of drying shrinkage microcracks from the source, and providing a stable dispersion and support environment for the self-healing microcapsules; the porous inorganic microcarrier inside the self-healing microcapsules can store sufficient sodium silicate repair agent. When cracks open, the outer wall material breaks, and the repair agent in the pores flows out fully, efficiently repairing and healing the residual cracks. The resulting cementitious products further densify the matrix microstructure, reducing the subsequent crack initiation and propagation. The two work together and promote each other, ultimately achieving a synergistic improvement in the material's self-healing efficiency.
[0072] The above description of the present invention is merely a preferred embodiment of the present invention and does not limit the implementation and protection scope of the present invention. Those skilled in the art should realize that any equivalent substitutions and obvious changes made using the present invention specification should be included within the protection scope of the present invention.
Claims
1. A self-healing geopolymer composite material resistant to shrinkage microcracks, characterized in that, By weight, including: 90-100 parts of activated aluminosilicate raw material; 35-55 parts of alkali activator; 4-8 parts of expanding agent; 3-5 portions of self-repairing microcapsules; 1 to 1.5 parts of reinforcing fiber; The alkali activator is a compound solution of sodium silicate and sodium hydroxide, the modulus of the alkali activator is 1.2-1.8, and the alkali activator accounts for 6%-10% of the total solid mass of the self-healing geopolymer composite material for resisting shrinkage microcracks, based on sodium oxide. The expanding agent is coated and modified active magnesium oxide; The self-healing microcapsule comprises a porous inorganic microcarrier, a sodium silicate repair agent loaded in the pores of the porous inorganic microcarrier, and an alkali-resistant material coating the outer surface of the porous inorganic microcarrier.
2. The composite material according to claim 1, characterized in that, The active silica-alumina raw material comprises, by weight, 60-70 parts fly ash, 20-30 parts slag, and 5-15 parts silica fume.
3. The composite material according to claim 1, characterized in that, The sodium silicate has a modulus of 3.0-3.5; the sodium hydroxide has a purity of not less than 99%.
4. The composite material according to claim 1, characterized in that, The expanding agent is active magnesium oxide with a passivation layer of magnesium carbonate, basic magnesium carbonate, or magnesium hydroxide on its surface.
5. The composite material according to claim 1, characterized in that, The alkali-resistant material is urea-formaldehyde resin or melamine-formaldehyde resin.
6. The composite material according to claim 1, characterized in that, The thickness of the alkali-resistant polymer wall material is 2μm to 10μm, and the particle size of the self-healing microcapsules is 50μm to 200μm.
7. The composite material according to claim 1, characterized in that, The sodium silicate repair agent is a sodium silicate solution with a modulus of 2.5-3 and a solid content of 40%.
8. The composite material according to claim 1, characterized in that, The reinforcing fiber is one or more of basalt fiber, polyvinyl alcohol fiber, or polypropylene fiber, and the length of the reinforcing fiber is 6mm to 9mm.
9. A method for preparing a self-healing geopolymer composite material resistant to shrinkage microcracks as described in any one of claims 1 to 8, characterized in that, Includes the following steps: Step 0: Mix fly ash, slag, and silica fume evenly to obtain the active aluminosilicate raw material; The sodium silicate and sodium hydroxide are compounded to form an alkaline activator with a modulus of 1.2-1.8; The active magnesium oxide is surface passivated in an atmosphere containing carbon dioxide and water vapor to form a passivation layer of magnesium carbonate, basic magnesium carbonate, or magnesium hydroxide on its surface. After drying, grinding, and sieving, the expanding agent is obtained. The dried porous inorganic microcarrier is immersed in sodium silicate repair agent. The sodium silicate repair agent is loaded into its pores by impregnation under normal pressure or vacuum. After removing the free liquid on the surface, the outer surface of the porous inorganic microcarrier is coated with the alkali-resistant material. After curing, drying and sieving, the self-healing microcapsules are obtained. Step 1: Add the expanding agent and the reinforcing fiber to the active aluminosilicate raw material, stir, and obtain a solid mixture; Step 2: Add the self-healing microcapsules to the solid mixture and continue stirring to obtain a dry mixture; Step 3: Slowly add the alkali activator to the dry mixture. The alkali activator accounts for 6%-10% of the mass of the dry mixture, based on sodium oxide. Stir to obtain the self-healing geopolymer composite material with anti-drying microcracks.